Fetal Alcohol Syndrome and Secondary Schizophrenia: A Unique Neuropathologic Study. (April 2015) - Stoos, Catherine; Nelsen, Laura; Schissler, Kathryn A.; Elliott, Amy J.; Kinney, Hannah C.
We report the unique neuropathologic study of an adult brain of a patient with fetal alcohol syndrome who developed the well-recognized complication of schizophrenia in adolescence. The major finding was asymmetric formation of the lateral temporal lobes, with marked enlargement of the right superior temporal gyrus, suggesting that alcohol is preferentially toxic to temporal lobe patterning during gestation. Critical maturational changes unique to adolescence can unmask psychotic symptomatology mediated by temporal lobe pathology that has been clinically dormant since birth. Elucidating the neuropathologic basis of the secondary psychiatric disorders in fetal alcohol syndrome can help provide insight into their putative developmental origins.